Discrete models on one-dimensional net with the preset Lie algebra of symmetries - Balinsky , A. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Poisson realizations of the classical YBZF-algebras are constructed from special examples using the simplest rational solution of the classical Yang-Baxter equation, the Poisson realization of a Lie algebra, the moment mapping, and a generalization of L-operators. Sufficient conditions under which additional constraints on the image of the moment mapping are satisfied are established.